2012
DOI: 10.1093/jrr/rrs086
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective effect on HepG2 cells of low concentrations of cobalt chloride: induction of hypoxia-inducible factor-1 alpha and clearance of reactive oxygen species

Abstract: It has been found that low doses of certain toxicants might generate a protective response to cellular damage. Previous data have shown that elevated doses of cobalt (Co) induce injury to cells and organisms or result in radiological combined toxicity. Whether low doses of Co generate a protective effect or not, however, remains controversial. In this study, we investigated the effect and mechanism of action of low dose cobalt chloride (CoCl2, 100 μM) on the viability of irradiated cells. 3-(4,5-Dimethylthiazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…We uniquely identified a subclone variant, J5 cells, that overexpressed HIF-1α protein normoxically, and the relative tolerance of these cells against a single fraction of radiation (20 Gy) was also overwhelmingly strong compared with the non-HIF-1α-expressing counterparts (Figure 1). This finding is consistent with a recent report by Jin et al [21], in which a forced expression of HIF-1α by CoCl 2 conferred radioprotection of hepatoma Hep G2 cells. We also reported previously that neutralization of normoxically overexpressed HIF-1α by YC-1, which is a naturally occurring HIF-1α inhibitor, sensitized J5 cells for efficacious eradication against a reactive oxygen species (ROS)-producing anti-cancer compound, arsenic trioxide (ATO) [22], which is similar to the ROS production manifested by RT.…”
Section: Discussionsupporting
confidence: 94%
“…We uniquely identified a subclone variant, J5 cells, that overexpressed HIF-1α protein normoxically, and the relative tolerance of these cells against a single fraction of radiation (20 Gy) was also overwhelmingly strong compared with the non-HIF-1α-expressing counterparts (Figure 1). This finding is consistent with a recent report by Jin et al [21], in which a forced expression of HIF-1α by CoCl 2 conferred radioprotection of hepatoma Hep G2 cells. We also reported previously that neutralization of normoxically overexpressed HIF-1α by YC-1, which is a naturally occurring HIF-1α inhibitor, sensitized J5 cells for efficacious eradication against a reactive oxygen species (ROS)-producing anti-cancer compound, arsenic trioxide (ATO) [22], which is similar to the ROS production manifested by RT.…”
Section: Discussionsupporting
confidence: 94%
“…It was demonstrated that OA might decrease the level of GSH via the inhibition of γ-GCS activity in hypoxic tumor cells. According to our previous study and other data, there was a higher level of cellular GSH in hypoxic cells or mimetic hypoxic cells compared with that in aerobic cells, resulting in the refractoriness of cells to irradiation (36,39,40). Therefore, the combination of OA and radiation to effectively destroy hypoxic tumor cells is strongly correlated with the inhibition of intracellular GSH biosynthesis.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, CoCl 2 can be universally used as a chemical reagent that induces biochemical and molecular responses similar to those observed under a hypoxic condition (37,38). Our previous results also showed that similar to hypoxia, CoCl 2 enhanced cellular radioresistance and increased the levels of HIF-1α (36). We selected two different concentrations of OA, with no obvious influence on cell viability, to carry out the present experiment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Shenoy et al 41 showed that HIF-1α enhanced DNA repair through upregulating XPA, which leads to cisplatin resistance in testicular germ cell tumors ( Table 1 ). In a study about the mechanism of chemo-/radioresistance in hepatocellular carcinoma, Jin et al 42 ( Table 1 ) demonstrated that HIF-1α inhibited the formation of both radiotherapy-induced DSBs and SSBs. Klein et al 43 ( Table 1 ) suggested that the HIF-1α-activated DNA damage repair pathway also has an emerging role in chemo-/radioresistance in gastric cancer.…”
Section: Hif-1α-mediated Activation Of Dna Repair Pathwaymentioning
confidence: 99%